The Role and Regulatory Network of the CiaRH Two-Component System in Streptococcal Species - He, Li-Yuan; Le, Yao-Jin; Guo, Zhong; Li, Sha; Yang, Xiao-Yan (Frontiers in Microbiology, 2021)
Pathogenic streptococcal species are responsible for a broad spectrum of human diseases ranging from noninvasive and localized infections to more aggressive and life-threatening diseases, which cause great economic losses worldwide. Streptococci possess a dozen two-component systems (TCSs) that play important roles in the response to different environmental changes and adjust the expression of multiple genes to successfully colonize and infect host cells. In this review, we discuss the progress in the study of a conserved TCS named CiaRH in pathogenic or opportunistic streptococci including Streptococcus pneumoniae, Streptococcus pyogenes, Streptococcus agalactiae, Streptococcus mutans, Streptococcus gordonii, Streptococcus sanguinis and Streptococcus suis, focusing on the function and regulatory networks of CiaRH, which will provide a promising strategy for the exploration of novel anti-streptococcal therapies. This review highlights the important role of CiaRH and provides an important basis for the development of anti-streptococcal drugs and vaccines.